Pemberdayaan Keluarga Melalui Pelatihan Pembuatan Teh Daun Kelor Bagi Masyarakat Desa Sea Mitra Kecamatan Pineleng Kabupaten Minahasa - Niode, Burhan; Sandiah, Nasrun (Universitas Sam Ratulangi, 2022)
Sea Mitra Village is one of the villages located in Pineleng District, Minahasa Regency. The results of observations show that in the yards of the houses of the people of Sea Mitra Village, many Moringa trees are found which are limited to being used as barriers to the yard of the house. In order to develop public knowledge about the efficacy of herbal plants and the development of family economic businesses, community empowerment activities were carried out in the form of training in making Moringa leaf tea. This training uses the method of discussion and demonstration plot (demplot). The results of the training showed that the participants really understood the content and efficacy of Moringa leaves for health because of the 20 participants, 95% very understanding of the material provided, and 5% quite understood the material provided. In addition, the participants understood the making of Moringa leaf tea. This was obtained through observations by the facilitator on the enthusiasm and work results of the participants. Keywords: moringa leaf tea; family empowerment; villagersAbstrakDesa Sea Mitra merupakan salah satu desa yang berada di Kecamatan Pineleng Kabupaten Minahasa. Hasil observasi menunjukan bahwa di pekarang-pekarang rumah dari masyarakat Desa Sea Mitra banyak ditemui pohon kelor yang terbatas dijadikan pembatas halalaman rumah. Guna mengembangkan pengetahuan masyarakat tentang khasiat tanaman herbal serta pengembangan usaha ekonomi keluarga maka dilaksanakanlah kegiatan pemberdayaan msyarakat berupa pelatihan pembuatan teh daun kelor. Pelatihan ini menggunakan metode ceramah, diskusi dan demonstrasi plot (demplot). Hasil pelatihan menunjukan bahwa para peserta sangat memahami kandungan dan khasiat dari daun kelor untuk kesehatan karena dari 20 peserta terdapat 95% sangat memahami materi yang diberikan, serta 5% cukup memahami materi yang diberikan. Disamping itu, para peserta memahami pembuatan teh daun kelor. Hal ini diperoleh melalui pengamatan oleh fasilitator terhadap antusiasme dan hasil kerja dari peserta.Kata kunci: teh daun kelor; pemberdayaan keluarga; masyarakat desa